Analisis Program Keluarga Harapan Dan Peningkatan Sumber Daya Manusia - Adnan, Adnan; Syahidin, Syahidin; Marwansyah, Marwansyah; Teniro, Alwin (inovator, 2022)
This study examines the influence of the Family Hope Program (PKH) on The Improvement of Human Resources. The data used is skunder data obtained from the Social Service Office of Central Aceh Regency, then analyzed using quantitative methods and analyzed with non-parametric statistics with the Pearson Chi-Square approach, to test the significance of the influence of the Family Hope Program (PKH) on the improvement of Human Resources (HR). From the results of data analysis, it was obtained that there was a significant influence of PKH on the improvement of human resources, because Chi-Square X² calculated at a significance level of 5% with (df = 4) obtained a value of 11.903 > 9.488 or Asymptotic Significance (2-sided), obtained by 0.018 < 0.05. Based on the findings of this study, it is recommended to the government to increase the provision of PKH benefits to the poor and for the beneficiary communities to take advantage of assistance according to the criteria, especially in the use of education funds so that the educational needs of school children are met.